A comprehensive evaluation of ecological isolation zones based on grey fixed-weight clustering - Zhang Gengjie; Yin Jing; Liu Zixin; Yang Huijie; Liu Shuxia; Hu Huiyong (E3S Web of Conferences)
Soil erosion is one of the common disasters in the red soil areas of the mountain plains, and the setting up of ecological isolation zone terraces has become a measure for the integrated management of soil erosion in farming areas. A comprehensive evaluation of the basic community characteristics, soil nutrients and other influencing factors after the installation of the ecological isolation zone terraces was carried out in 2016 and 2022 in combination with the grey fixed-weight clustering method. The results showed that among the five grey categories of ‘Better’, ‘Good’, ‘Fair’, ‘Poor’ and ‘Worse’, the basic community characteristics in 2022 was in the ‘Poor’ grey category, the soil nutrients was ‘Poor’ and other influencing factors was ‘Good’. The three categories’ maximum grey weighted clustering coefficients were 0.4734, 0.2496 and 0.9171. In 2016, the grey categories for basic community characteristics and soil nutrients were both ‘Worse’, with maximum grey weighted clustering coefficients of 0.8068 and 0.2828 respectively, while the other influencing factors was in the ‘Better’ grey category, with a maximum grey weighted clustering coefficient of 0.5240. Overall, the condition of the ecological isolation zone terraces in 2022 was better than in 2016. In addition, this paper took the prospects on the maintenance of ecological isolation zone terraces, the demand of vegetation for nutrients, the optimisation of the structure of ecological isolation zone terraces, and the construction of an evaluation index system, with a view to providing a theoretical basis and scientific basis for the subsequent establishment of ecological isolation zone terraces and promoting their wide application in agriculture and ecology.